2001
DOI: 10.1080/15604280212526
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor‐Dependent Proliferation of the Pancreatic β‐cell Line βTC‐tet: An Assay for β‐cell Mitogenic Factors

Abstract: The ability to expand normal pancreatic islet β cells in culture would significantly advance the prospects of cell therapy for diabetes. A number of growth factors can stimulate limited islet cell replication, however other factors may exist which are more effective β-cell-specific mitogens. The search for novel β-cell growth factors has been hampered by the lack of a β-cell-specific proliferation assay. We developed a simple and sensitive assay for β-cell growth factors based on a conditionally-transformed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The MIN6 cell line secreted approximately 3 times more insulin but much lower amounts of IGF-II and vesiculin than the BTC6-F7 cell line. Both vesiculin and IGF-II were secreted in much lower quantities than total insulin; these concentrations of IGF-II are close to those previously shown to stimulate ␤-cell proliferation (4,24).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The MIN6 cell line secreted approximately 3 times more insulin but much lower amounts of IGF-II and vesiculin than the BTC6-F7 cell line. Both vesiculin and IGF-II were secreted in much lower quantities than total insulin; these concentrations of IGF-II are close to those previously shown to stimulate ␤-cell proliferation (4,24).…”
Section: Resultssupporting
confidence: 85%
“…Two 10-L injections were performed per sample. To prepare a 5-point standard curve, 1 mL of nonconditioned medium (serum-free, phenol red-free with 0.1% BSA [w/v]) was constituted with peptide (2,4,8,16, and 40 ng/mL of vesiculin; 80, 40, 20, 10, and 5 ng/mL of IGF-II) and processed through SPE columns as above. A second 5-point standard curve, which encompassed the lower limit of detection for vesiculin, was analyzed; this consisted of 1 mL of nonconditioned media constituted with vesiculin (0.1, 0.5, 1, 2, and 4 ng/mL vesiculin).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread (Petrik et al 1999) or local (Devedjian et al 2000;Okamoto et al 2006) overexpression of Igf2 has been shown to promote islet cell hyperplasia, and application of Igf2 to betacells in culture induces proliferation (Milo-Landesman and Efrat 2002). Recent genome-wide association studies have identified genetic variants in IGF2BP2 that are associated with type 2 diabetes in human patients (Saxena et al 2007;Scott et al 2007;Zeggini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…IGF2 has been shown to promote pancreatic b-cell survival against apoptotic stimuli in vitro and in vivo (Rabinovitch et al 1982, Swenne et al 1987, Hogg et al 1993, Ilieva et al 1999, Robitaille et al 2003, Jourdan et al 2011 and induce proliferation in a growth-arrested mouse b-cell line (Milo-Landesman & Efrat 2002). IGF2 protects pre-diabetic NOD mouse islets from the cytotoxic actions of IL1b by the mechanisms that include a reduction in apoptosis (Hill et al 1999b).…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%